The House Key : House as key to understanding ACTS (the micro-text) within its Roman Imperial Context (the macro-text) - O'Keefe, Anne (Trinity College (Dublin, Ireland). School of Hebrew, Biblical and Theological Studies, 2002)
While "house" has long been recognized as key to understanding Christianity and its world, my contention is that its analytical potential has actually been under-utilized by scholars. The study demonstrates how conscious use of the broad, flexible concept of "house" results in a valuable analytical tool which in turn sheds new light on Acts in its Roman imperial social world.
Keywords: Hebrew Biblical and Theological Studies, Ph.D.; Ph.D. Trinity College Dublin